Analysis Of Bid Ask Spread And Volume Transaction Against The Holding Period (E-Jurnal Akuntansi, 2026)
This research aims to analyze the influence of Bid Ask Spread and Transaction Volume on the Holding Period of two indices, namely JII and LQ45. The data used consists of secondary data, including the total value from market opening to closing, daily Bid Ask Spread data, Transaction Volume, and Holding Period of both indices over one month. The population and sample in this study are 30 JII companies and 45 liquid LQ45 companies for the period of 2024. This quantitative research employs descriptive analysis techniques, classical assumption tests, and multiple regression tests to examine the relationship between Bid Ask Spread and Transaction Volume on the holding period. The results indicate that Bid Ask Spread affects the Holding Period of both indices, as a higher spread leads investors to hold their shares longer. Additionally, Transaction Volume also influences the holding period of both indices, as liquid stocks tend to have a longer holding period. This provides insights for investors to design strategies and enhance the attractiveness of their stocks.
Keywords: Holding Period; Bid Ask Spread; Transaction Volume